Effect of rutin on in vitro maturation of sheep oocytes from in vitro cultured preantral follicles - Torres, Maria Lilian Gomes Loiola; Andrade, Kíscyla Oliveira de; Silva, Regina Lucia dos Santos; Monte, Alane Pains Oliveira do; Guimarães, Valéria da Silva; Oliveira Junior, Joãozito Liandro; Souza, Luanna Mendes; Santos, Gabriela Cristina da Silva; França, Anna Thaylla Venceslau; Matos, Maria Helena Tavares de (Semina: Ciências Agrárias, 2024)
The aims of this study were to determine the effect of rutin on in vitro maturation (IVM) of oocytes from in vitro-grown sheep secondary follicles and to analyze the possible involvement of the mammalian target of rapamycin (mTOR) pathway in IVM under the influence of rutin. Secondary follicles were cultured for 18 days in α-Minimum Essential Medium (α-MEM) supplemented with bovine serum albumin (BSA), insulin, glutamine, hypoxanthine, transferrin, selenium, ascorbic acid, and leptin (control medium: α-MEM+). Next, the follicles were evaluated for morphology, antrum formation, and follicular diameter, and the rate of fully grown oocytes (≥110 µm). Fully grown oocytes were submitted to IVM in Tissue Culture Medium 199 (TCM199) supplemented with fetal bovine serum (FBS), luteinizing hormone (LH), and recombinant follicle-stimulating hormone (rFSH) (IVM control medium), or in this medium with 0.1, 1, or 10 µg mL-1 rutin. At the end of IVM, the oocytes were evaluated for mitochondrial activity, the reactive oxygen species (ROS) and glutathione (GSH) levels, the percentage of meiotic resumption, DNA fragmentation, and mTOR pathway involvement. After 18 days of in vitro culture, 77.5% of the follicles were normal and 77.7% became antral follicles with a diameter of 380.41 µm. Furthermore, almost 70% of the oocytes grew in vitro, reaching a diameter ≥110 µm and were submitted to IVM. Supplementation with 10 µg mL-1 rutin significantly increased the percentage of oocytes that resumed meiosis (47.27%) compared with the control medium (30.43%). There was a significant increase in the ROS and GSH levels in oocytes matured with 0.1 µg mL-1 rutin compared with the other rutin treatments (p < 0.05). Furthermore, oocytes matured with TCM199+ showed a higher (p < 0.05) percentage of DNA fragmentation (30%) than those that matured with 10 µg mL-1 rutin (0%). After IVM, oocytes matured in the presence or absence of rapamycin showed a similar percentage of meiotic resumption (61.76% for TCM199+ 10 µg mL-1 rutin and 70.73% for TCM + 10 µg mL-1 rutin + rapamycin; p > 0.05). In conclusion, supplementation with 10 µg mL-1 rutin increased meiosis resumption and reduced DNA damage.